2018
DOI: 10.1038/s41598-018-21378-x
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid resistance levels of Mycobacterium tuberculosis can largely be predicted by high-confidence resistance-conferring mutations

Abstract: The majority of Mycobacterium tuberculosis isolates resistant to isoniazid harbour a mutation in katG. Since these mutations cause a wide range of minimum inhibitory concentrations (MICs), largely below the serum level reached with higher dosing (15 mg/L upon 15–20 mg/kg), the drug might still remain partly active in presence of a katG mutation. We therefore investigated which genetic mutations predict the level of phenotypic isoniazid resistance in clinical M. tuberculosis isolates. To this end, the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 30 publications
6
94
2
1
Order By: Relevance
“…Previous studies had more than one gene mutations exhibiting a higher MIC range. 5,18,25,26 However, in our study, we detected only a single gene mutation.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…Previous studies had more than one gene mutations exhibiting a higher MIC range. 5,18,25,26 However, in our study, we detected only a single gene mutation.…”
Section: Discussioncontrasting
confidence: 64%
“…26 Recent studies have shown that these uncommon gene mutations may be susceptible or have low-/high-level resistance to isoniazid. 5,26 WHO recommends that DSTs of both phenotypes and genotypes should be used for all isolates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in most settings misclassifications of double mutants would be rare compared with the increased ability to detect inhA promoter mutants with a higher clinical breakpoint. Second, the effect of these coding mutations on the INH MIC and thus clinical outcome is likely modest at worst, but more MIC data are needed for the mutations at different inhA codons (20-23). Nevertheless, it might be advisable for countries that conduct routine WGS to err on the side of caution by classifying these double mutants as high-level resistant until clinical data to the contrary are available (in practice, however, it would be challenging to conduct a sufficiently powered study to address this question as these mutations are so rare).…”
Section: Manuscriptmentioning
confidence: 99%